(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Futsal is a sport that requires not only physical and technical abilities but also psychological factors that support performance, one of which is self-efficacy. Self-efficacy reflects an individual’s belief in their ability to successfully perform specific tasks and overcome challenges encountered during sports activities. In futsal extracurricular programs, confidence is considered an important factor that may influence students’ technical performance, particularly in dribbling skills. Therefore, this study aimed to determine the relationship between self-efficacy and the dribbling technique performance of male students participating in futsal extracurricular activities at SMA Negeri 12 Bandar Lampung. This study employed a quantitative method with a correlational approach. The sample consisted of 30 male students selected using a total sampling technique. Data were collected using a self-efficacy questionnaire and a zig-zag dribbling test. The collected data were analyzed through descriptive statistics, Pearson Product Moment correlation analysis, and simple linear regression. The findings revealed that the majority of students possessed high levels of self-efficacy and demonstrated good dribbling performance. The Pearson Product Moment correlation analysis showed a correlation coefficient of r = -0.904, which was greater than the critical value (r calculated > r table; 0.904 > 0.361), with a significance value of 0.000 < 0.05. These results indicate a very strong and statistically significant relationship between self-efficacy and dribbling technique performance. The negative correlation suggests that students with higher self-efficacy required less time to complete the dribbling test, indicating better performance. In conclusion, self-efficacy has a very strong and significant relationship with the dribbling technique performance of male students in futsal extracurricular activities. Enhancing students’ confidence may contribute positively to improving their technical performance in futsal.